Intraoperative blood loss and blood transfusion requirements in patients undergoing orthognathic surgery - Faverani, Leonardo Perez [UNESP]; Ramalho-Ferreira, Gabriel; Fabris, André Luis Silva; Polo, Tárik Ocon Braga; Poli, Guilherme Henrique Souza; Pastori, Cláudio Maldonado; Marzola, Clóvis; Assunção, Wirley Gonçalves; Garcia-Júnior, Idelmo Rangel (Springer, 2014)
Procedures for the surgical correction of dentofacial deformities may produce important complications, whether due to the potential for vascular injury or to prolonged surgery, both of which may lead to severe blood loss. Fluid replacement with crystalloid, colloid, or even blood products may be required. The aim of this study was to assess blood loss and transfusion requirements in 45 patients (18 males and 27 females; mean age 29.29 years, range 16-52 years) undergoing orthognathic surgery, assigned to one of two groups according to procedure type-rapid maxillary expansion or double-jaw orthognathic surgery. Preoperative hemoglobin and hematocrit levels and intraoperative blood loss were measured. There was a substantial individual variation in pre- and postoperative hemoglobin values (10.3-17 and 8.8-15.4 g/dL, respectively; p < 0.05). Mean hematocrit values were 41.53 % preoperatively (range 31.3-50.0 %) and 36.56 % postoperatively (range 25-43.8 %) (p < 0.05). Mean blood loss was 274.60 mL (range 45-855 mL). Only two patients required blood transfusion. Although blood loss and transfusion requirements were minimal in the present study, surgical teams should monitor the duration of surgery and follow meticulous protocols to minimize the risks.
Keywords: Blood loss; Hypovolemic; Hematocrit; Blood transfusion